The effect of climatic factor toward the population of rhinoceros beetles in oil palm plantation / Nur Shahida Rahim - Rahim, Nur Shahida (Faculty of Plantation and Agrotechnology, 2018)
Oil palm was been introduced to Malaysia in year 1911.Started of the year, oil palm plants have highly developed to become the number one important crop of the country. However there are many obstacles like rhinoceros beetles as the pest in oil palm plantation that reduce the production of oil palm and its sustainability in country. This study to determine the population of this pest in selected area, whereas at the Marang, Terengganu and determine the relationship between climatic factors (Rainfall, temperature) and O. rhinoceros.The pheromone trap were used to collect the population O.rhinoceros and using rainfall and temperature data from meteorology office to determine the relationship between climatic factors (Rainfall, temperature) with pest. These analyses have been done by using Microsoft Excel and SPSS software. The result shows that the p- value 0.001 that shows there was a significant difference in mean RB number between Area I and Area II. The result shows that the P > 0.000 where the study need to accept the null hypothesis. Hence the result means that there is statistically significant correlation between temperature and beetles population. But result shows the p>0.126 so, the null hypothesis is need to reject. Hence the result means that there is not significant. In conclusion, other than rainfall and temperature, there are another factor that effect of population rhinoceros beetles in oil palm plantation such as soil pH, humidity, cover crop and others.